Perbedaan Keseimbangan Postural Wanita Obesitas Peserta Senam Zumba di Pusat Kebugaran Bandar Lampung - A.A. Mas Maharani; Khairun Nisa Berawi; Muhammad Iqbal (CV. Jasa Sukses Abadi, 2026)
Women have a greater risk become obese due to puberty. People with obesity or greater body mass index (BMI) have a poor postural balance. Muscle strength is one of the factors affect postural balance. Muscle strength can be trained with physical activity and zumba is one of physical activity which collaborate music, dance, and cardio. The aim of this study is to find out postural balance differences among obese woman who participate zumba exercise. This study is an unpaired quantitative analysis with a cross-sectional design. The study was conducted at De Perkasa Fitness Center with a total sample of 80 people. Data were collected by examining body weight, height, and postural balance using the berg balance scale test on obese women who participate zumba exercise. The data obtained were tested using the Saphiro Wilk test to find out the normality of data and continued with the Mann-Whitney test. The average results of postural balance in the routine and first-time groups, respectively, were 54.5 ± 1.377 and 51.95 ± 1.648. The results of the Mann-Whitney test showed that p value = 0.000 (p<0.05) showed a significant difference (p<0.05) between the postural balance of obese women participating in zumba exercise. There are differences in the postural balance of obese women participating in zumba exercise at fitness center in Bandar Lampung.